Prediction of large bias-dependent magnetoresistance in al l-oxide magnetic tunnel junctions with a ferroelectric barrier - SANVITO, STEFANO; CAFFREY, NUALA; ARCHER, THOMAS; RUNGGER, IVAN (My University, 2011)
All-oxide magnetic tunnel junctions (MTJs) incorporating functional materials as insulating barriers have the potential of becoming the founding technology for novel multifunctional devices. We investigate, by first-principles density functional theory, the bias-dependent transport properties of an all-oxide SrRuO3/BaTiO3/SrRuO3 MTJ. This incorporates a BaTiO3 barrier which can be found either in a nonferroic or in a ferroelectric state. In such an MTJ not only can the tunneling magnetoresistance reach enormous values, but also, for certain voltages, its sign can be changed by altering the barrier electric state. These findings pave the way for a new generation of electrically controlled magnetic sensors.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; magnetic tunnel junctions (MTJs); Nanoscience & Materials